When thinking you are better leads to feeling worse: Self-other asymmetries in pro-social behavior and increased anxiety during Covid-19. - Chelsea Helion; Virginia Ulichney; David V Smith; Johanna Jarcho (PLoS ONE, 2023)
Self-serving biases (e.g., beliefs that one tends to perform better than peers) are generally associated with positive psychological outcomes like increased self-esteem and resilience. However, this tendency may be problematic in the context of collective action problems, wherein individuals are reliant on others' pro-social behaviors to achieve larger goals. We examined this question in the context of the Covid-19 pandemic, and recruited participants for an online study (n = 1023) from a university community in Spring 2020. We found evidence for self-peer asymmetries in Covid-related knowledge and restriction behavior, such that participants reported that they knew more about Covid-related symptoms, were doing more to stop the spread of the disease, and were more pro-socially motivated in doing so than peers. Actual peer reports indicated that these were overestimations. This self-enhancement comes with a cost: the perceived self-peer restriction behavior asymmetry had an indirect effect on the positive relationships both from Covid-specific worry and from perceived stress to general anxiety symptom intensity during the early lockdown period. People tended to have more severe symptoms of anxiety when they were more worried about Covid-19 and when they reported greater perceived stress, especially when they underestimated others' contributions to public health action relative to their own. This suggests that lack of trust in others' pro-sociality may be personally maladaptive for mental health.